Development of Coaching for Science Teachers in Khon Kaen Municipality Schools - Maenyat, Suthasini (Journal of Teacher Professional Learning Community (JTPLC) (Online), 2022)
This paper aimed to develop coaching protocol for science teachers in Khon Kaen municipality schools. Research instruments included 1) questionnaire of appropriate components and indicators of coaching for science teachers in Khon Kaen municipality; 2) questionnaire of the status quo and need of coaching for science teachers in Khon Kaen municipality schools; 3) interview form for supervision best practices schools; and 4) questionnaire of appropriation and plausibility of coaching protocol for science teachers in Khon Kaen municipality schools. Data analysis is descriptive statistics including percentages, mean, and standard deviation. Results showed the key issues as follows. First, overview of the status quo of coaching for science teachers in Khon Kaen municipality schools represents in the low level. However, the overview of the need for coaching for science teachers was at the good level. Second, coaching protocol for science teachers in Khon Kaen municipality schools consists of 1) rationales, 2) goals, 3) coaching protocol, 4) administrative mechanisms, and 5) key success. Overview of appropriation and plausibility of coaching protocol for science teachers in Khon Kaen municipality schools was at a very high level.